Analgesics for Dental Implants: A Systematic Review - Melini, Matteo; Forni, Andrea; Cavallin, Francesco; Parotto, Matteo; Zanette, Gastone (Frontiers in Pharmacology, 2021)
Post-surgical pain is commonly associated with dental and oral surgery, and the use of analgesics has been investigated in the management of post-operative pain. This systematic review summarizes available evidence on analgesics used to manage dental implants surgery post-operative pain, to identify best therapeutic protocols and knowledge gap. A comprehensive search was conducted including MEDLINE/Pubmed, EMBASE, SCOPUS, clinicaltrials.gov and the Cochrane Database of Systematic Reviews through May 2020. Only randomized controlled trials were included. PRISMA guidelines were followed and risk of bias was appraised using Cochrane RoB2 tool. Eleven trials (762 patients overall) were included. Some aspects limited the feasibility of a meaningful meta-analysis, thus a narrative synthesis was conducted. Risk of bias was low in four studies and high in two studies, while five studies raised some concerns due to the randomization process. Analgesics use seemed to be associated with improved postoperative outcomes (pain, patient’s satisfaction and need for rescue medication) when compared to placebo. Overall, this review suggests that the administration of analgesics may provide some advantages in the management of postoperative outcomes after dental implant placement, while indications about the best analgesics cannot be provided.